Perceptions and acceptability of microsampling in children and young people: a single-centre survey - Jennifer Preston; Alan Salama; Louise Oni; Julien Marro; Andrew J Chetwynd; Laura Whitty; Sammy Ainsworth (BMJ Publishing Group, 2022)
Background The use of at home microsampling devices, such as dried aliquots of blood and urine, for scientific research has expanded in recent years. These devices collect small volumes of biofluids which air dry and can be posted to central laboratories. In general, they are cheaper and more convenient, saving patients travel time and freeing up staff. In adult populations, this sampling method is well perceived, with >90% of samples being of adequate size and quality for scientific research. However, little literature on microsampling in paediatric populations exists. The aim of this study was to explore the perceptions and acceptability of microsampling in children and young people.Methods Online patient and public involvement was obtained by attending the Generation R Young Person's Advisory Group Liverpool, to explore the perceptions of at home microsampling. During the session, the rationale and use of microsampling was demonstrated. The participants provided informal feedback during the interactive session and completed a short online questionnaire.Results A total of 13 children and young people attended the event and they were aged 10-17 years, of these 10 responded to an online questionnaire. The general feedback on microsampling was positive with 80% of respondents indicating they would be willing to participate in at home microsampling studies. Furthermore, 100% respondents reported being willing to provide both biofluids on a monthly basis and 40% would be willing to provide dried urine samples weekly.Conclusions Children and young people are supportive of at home microsampling for research purposes and this offers the possibility of widening participation to research.